A Pathogen-Responsive Leucine Rich Receptor Like Kinase Contributes to Fusarium Resistance in Cereals - Thapa, Ganesh; Gunupuru, Lokanadha R.; Hehir, James G.; Kahla, Amal; Mullins, Ewen; Doohan, Fiona M. (Frontiers in Plant Science, 2018)
Receptor-like kinases form the largest family of receptors in plants and play an important role in recognizing pathogen-associated molecular patterns and modulating the plant immune responses to invasive fungi, including cereal defences against fungal diseases. But hitherto, none have been shown to modulate the wheat response to the economically important Fusarium head blight (FHB) disease of small-grain cereals. Homologous genes were identified on barley chromosome 6H (HvLRRK-6H) and wheat chromosome 6DL (TaLRRK-6D), which encode the characteristic domains of surface-localized receptor like kinases. Gene expression studies validated that the wheat TaLRRK-6D is highly induced in heads as an early response to both the causal pathogen of FHB disease, Fusarium graminearum, and its’ mycotoxic virulence factor deoxynivalenol. The transcription of other wheat homeologs of this gene, located on chromosomes 6A and 6B, was also up-regulated in response to F. graminearum. Virus-induced gene silencing (VIGS) of the barley HvLRRK-6H compromised leaf defense against F. graminearum. VIGS of TaLRRK-6D in two wheat cultivars, CM82036 (resistant to FHB disease) and cv. Remus (susceptible to FHB), confirmed that TaLRRK-6D contributes to basal resistance to FHB disease in both genotypes. Although the effect of VIGS did not generally reduce grain losses due to FHB, this experiment did reveal that TaLRRK-6D positively contributes to grain development. Further gene expression studies in wheat cv. Remus indicated that VIGS of TaLRRK-6D suppressed the expression of genes involved in salicylic acid signaling, which is a key hormonal pathway involved in defence. Thus, this study provides the first evidence of receptor like kinases as an important component of cereal defence again Fusarium and highlights this gene as a target for enhancing cereal resistance to FHB disease.